the Studying the city of Hamas need for fixed services to implement sustainable planning using geographic information systems software. (Journal of Hama University, 2024)
Sustainable planning is one of the most important foundations that must be taken into account when developing any modern city, in order to achieve environmental, economic and social sustainability in the general form of the city.The research aims to study the needs of some neighborhoods in the city of Hama for services under the current circumstances in order to implement sustainable planning, as three areas in the city of Hama were taken for study (Al-Sharia area - Al-Sabuniyah area - South Al-Malaab area) to solve the social problems resulting from the repercussions of the crisis in terms of providing... Multiple educational, health, and living services to develop proposals and then solve these problems in the future.The study models were built using Geographic Information Systems (GIS) software. Several future scenarios were studied to provide us with a better vision for managing these services in the study areas.Through the study, it was found that educational services provided to citizens in the neighborhoods need to be increased in number in line with the standard approved by the Ministry, while health services were fully covered according to the studied scenarios. As for the number of pharmacies, it is insufficient and work must be done to increase them until full service is achieved, and this applies. On those who approve bread and those who approve gas.This study helps decision-makers determine the city’s real needs for fixed services that contribute to improving the quality of life and developing areas of work and investment by supporting decision-makers and knowing the economic impact of implementing any scenario and its impact on the service reality.
Keywords: : Decision support system, GIS, sustainability